2018
DOI: 10.1039/c8qo00122g
|View full text |Cite
|
Sign up to set email alerts
|

Fused donor–acceptor π-conjugated diazatruxenones: synthesis and electronic properties

Abstract: A promising candidate for ambipolar charge transport: a disk-like platform, diazatruxenone, as a novel, compact and planar donor–acceptor molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…However, the inerasable property suggested that holes were insufficiently injected into the electret, which hindered the recombination with trapped electrons due to the significant difference between their HOMO energy levels. In regard to the results from p‐type and n‐type devices, it was interestingly found that the Poly CD exhibited ambipolar characteristics to trap holes or electrons by employing different types of semiconductors, which were attributed to the donor–acceptor structure of the CD unit …”
Section: Resultsmentioning
confidence: 99%
“…However, the inerasable property suggested that holes were insufficiently injected into the electret, which hindered the recombination with trapped electrons due to the significant difference between their HOMO energy levels. In regard to the results from p‐type and n‐type devices, it was interestingly found that the Poly CD exhibited ambipolar characteristics to trap holes or electrons by employing different types of semiconductors, which were attributed to the donor–acceptor structure of the CD unit …”
Section: Resultsmentioning
confidence: 99%
“…Besides triphenylene, other molecular systems were studied in recent years, such as those based on triindole [ 208 , 209 ], phthalocyanine [ 125 , 210 ], thiophene [ 211 , 212 ] and truxenone [ 213 , 214 ] cores, or on particular molecular architectures, such as dendrons [ 174 , 176 , 215 , 216 ]. Nakawa and coworkers reported the study of the mesomorphic and mobility properties of a blend of 1,4,8,11,15,18,22,25-octahexylphthalocyanine (C6PcH2) with its analogue 1,4,8,11,15,18,22,25-octahexyltetrabenzotriazaporphyrin (C6TBTAPH2) [ 125 ].…”
Section: Recent Advances In the Study Of Discotic Liquid Crystalsmentioning
confidence: 99%
“…Note that similar observations have been previously reported for the isolated trigonal building units. [40][41][42] (ii) Considering the effects of the p-bridge, the insertion of a phenylene spacer between the cores exerts a slight impact on the HOMO and LUMO energy levels when compared to the directly connected systems, suggesting a minor influence on the p-electron delocalization between platforms. This is in consonance with the similar distortions found for both the directly connected and phenylene-bridged systems.…”
Section: Molecular Fragmentsmentioning
confidence: 99%
“…[36][37][38][39] However, while isolated truxene-based molecules have been amply theoretically explored, a systematic study of their 2D conjugated polymers has not yet been reported. [40][41][42] In this work, we performed an exhaustive investigation of truxene-based 2D conjugated polymers with the aim to explore their chemical structure-electronic property relationships to guide the design of novel optimized 2D materials. To this end, we combined an oligomer approach with periodic boundary conditions (PBC) calculations for the 2D lattices.…”
Section: Introductionmentioning
confidence: 99%